MEMS : introduction and fundamentals - Gad-el-Hak, Mohamed, 1945- (The MEMS handbook, 2006)
As our knowledge of MEMS continues to grow, so does The MEMS Handbook. The field has changed so much that this Second Edition is now available in three volumes. Individually, each volume provides focused, authoritative treatment of specific areas of interest. Together, they comprise the most comprehensive collection of MEMS knowledge available, packaged in an attractive slipcase and offered at a substantial savings. This bestselling handbook is now more convenient than ever, and its coverage is unparalleled. MEMS: Introduction and Fundamentals